The Role of Lymph Node Dissection in the Treatment of Bladder Cancer - Cattaneo, Francesco; Motterle, Giovanni; Zattoni, Filiberto; Morlacco, Alessandro; Dal Moro, Fabrizio (Frontiers in Surgery, 2018)
Lymph node dissection (LND) is an essential component of radical cystectomy (RC) for bladder cancer. However, the optimal anatomical extent of LND and its potential therapeutic role are still controversial. Moreover, there is large uncertainty on the role of surgery in the setting of patients with clinically-positive nodes. In this review we will provide a synthesis of the available evidence on this highly debated topic.